Case report: Recurrent lung infections following treatment with pralsetinib for an elderly patient with RET-fusion positive NSCLC - An, Li; Chen, Pengzhi; Wang, Junfeng; Qin, Xuebing; Liu, Tingting; Gao, Yanhong; Wang, Peng; Zhang, Dong; Fang, Xiangqun; Zhang, Zhijian (Frontiers in Oncology, 2022)
Patients with RET fusions represent 1-2% of all cases of non-small cell lung cancer (NSCLC), the majority of whom are younger, and are extremely rare in the elderly. As a selective RET inhibitor, pralsetinib has been shown to be efficacious and well-tolerated in patients with RET-fusion NSCLC. Nevertheless, there are currently insufficient data available for assessing the activity and safety of pralsetinib in elderly patients with NSCLC. Herein, we report an 81-year-old NSCLC patient with KIF5B-RET fusion, who achieved stable disease for more than 9 months at a low-dose of pralsetinib as second-line therapy. Of particular note, during pralsetinb therapy, his clinical course was complicated by cryptococcal pneumonia and staphylococcus aureus lung abscess. Our study demonstrates that pralsetinib is an effective therapeutic option that provides survival benefits for elderly NSCLC patients harboring RET fusion. However, during pralsetinb therapy, treating physicians should maintain particular vigilance for the increased risk of infection, especially in elderly patients.